The intrinsically disordered CARDs‐Helicase linker in RIG‐I is a molecular gate for RNA proofreading. (19th April 2022) - Schweibenz, Brandon D; Devarkar, Swapnil C; Solotchi, Mihai; Craig, Candice; Zheng, Jie; Pascal, Bruce D; Gokhale, Samantha; Xie, Ping; Griffin, Patrick R; Patel, Smita S
Abstract: The innate immune receptor RIG‐I provides a first line of defense against viral infections. Viral RNAs are recognized by RIG‐I's C‐terminal domain (CTD), but the RNA must engage the helicase domain to release the signaling CARD (Caspase Activation and Recruitment Domain) domains from their autoinhibitory CARD2:Hel2i interactions. Because the helicase itself lacks RNA specificity, mechanisms to proofread RNAs entering the helicase domain must exist. Although such mechanisms would be crucial in preventing aberrant immune responses by non‐specific RNAs, they remain largely uncharacterized to date. This study reveals a previously unknown proofreading mechanism through which RIG‐I ensures that the helicase engages RNAs explicitly recognized by the CTD. A crucial part of this mechanism involves the intrinsically disordered CARDs‐Helicase Linker (CHL), which connects the CARDs to the helicase subdomain Hel1. CHL uses its negatively charged regions to antagonize incoming RNAs electrostatically. In addition to this RNA gating function, CHL is essential for stabilization of the CARD2:Hel2i interface. Overall, we uncover that the CHL and CARD2:Hel2i interface work together to establish a tunable gating mechanism that allows CTD‐chosen RNAs to bind the helicase domain, while at the same time blocking non‐specific RNAs. These findings also indicate that CHL could represent a novel target for RIG‐I‐based therapeutics. Synopsis: To release its autoinhibitory conformation, the innate immune receptor RIG‐I helicase domain must bind RNA, but it is not fully understood how specificity for viral RNA is ensured. Here, the CARDs‐Helicase linker (CHL) is identified as a regulatory element that functions together with the CARD2:Hel2i interface to establish a tunable gating mechanism for self/non‐self discrimination. The 56 aa CARDs‐Helicase linker (CHL) is a regulatory unstructured region in RIG‐I CHL stabilizes the autoinhibitory CARD2:Hel2i interface to keep RIG‐I in a signaling‐silent state CHL shields the helicase and electrostatically competes with incoming RNAs CHL and CARD2:Hel2i interface synergistically block self RNAs from activating RIG‐I Abstract : Specificity for RNA‐binding mediated activation of RIG‐I is ensured by a gating mechanism involving the CHL and CARD:Hel2i interface.